Математическая модель гидравлического сопротивления фильтра твердых частиц дизеля. Часть 2: температурный коэффициент - Кондратенко, Александр Николаевич (НТУ "ХПИ", 2014)
Описана математическая модель гидравлического сопротивления фильтра твердых частиц (ФТЧ) дизеля в реальных условиях эксплуатации. Модель построена на основе расходной характеристики одного модуля ФТЧ, экспериментально полученной при постоянной температуре текучей среды, и данных стендовых испытаний автотракторного дизеля 2Ч10,5/12, оснащенного полноразмерным ФТЧ. Модель позволяет учесть ряд факторов, характеризующих условия эксплуата- ции ФТЧ в составе выпускной системы этого дизеля. Учет этих факторов производится путем введения соответствующих коэффициентов. В данной части работы описан физический смысл и оценены значения температурного коэффициента модели, позволяющего учесть изменение температуры отработавших газов на входе в корпус фильтра как функцию среднего эффективного давления дизеля

The paper deals with a mathematical model describing hydraulic resistance of a diesel particulate matter filter (DPF) under real operating conditions. The model is based on the flow characteristics of a single module of the DPF filter element obtained experimentally for a constant temperature of fluid, and data of bench tests of autotractor diesel 2Ch10.5/12 equipped with a full-sized DPF. The model also allows taking into account a number of factors that characterize operating conditions of the DPF in exhaust system of this diesel by introducing respective coefficient. The dependence of these coeffi¬cients on the operating and design parameters of diesel 2Ch10.5/12 is experimentally obtained and de¬scribed using the method of linear regression. In this part of the research we describe the physical meaning and evaluate the temperature coefficient of this mathematical model, which allows taking into account changes of the temperature of the exhaust gas at the filter housing inlet by the function of the mean effective pressure of the diesel. Using flow characteristics of the exhaust stream, such as mass flow rate per unit area of the inlet section of the module, when designing a DPF allows taking into ac¬count the model dimensions of the model and the number of the filter element modules
Mathematical model of the hydraulic resistance of the diesel particulate matter filter. Part 2: temperature coefficient
Keywords: прозрачный макет модуля; безмоторная исследовательская установка; макетный образец; фильтрующий элемент; diesel; particulate filter; hydraulic resistance; mathematical model